2019
DOI: 10.1002/best.201900026
|View full text |Cite
|
Sign up to set email alerts
|

Spannungsumlagerungen bei ermüdungsbeanspruchten Spannbetonbalken im numerischen Modell und Versuch

Abstract: Aufgrund einer Ermüdungs-Biegebeanspruchung kommt es in stärker beanspruchten Bereichen von Betonquerschnitten zu einer Materialdegradation und einer Steifigkeitsverringerung. Als Folge lagern sich Spannungen von den degradierten Bereichen in weniger degradierte Bereiche um. Dies führt auf der Bauteilebene zu einer Verlängerung der Lebensdauer der beanspruchten Strukturen. Die derzeit gültigen Normen [1][2][3] und Richtlinien [4] zur Bemessung von Windenergieanlagen berücksichtigen diese Effekte nur unzureiche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…The propagation of fatigue at the structural level has been recently investigated experimentally in several studies. 108,122,123 An example of the monitored propagation of fatigue degradation in an externally prestressed beam 108 is shown in Figure 6a. The test setup provided detailed data on the structural compressive fatigue behavior of concrete along with the strain field evolution during the fatigue life using advanced measurement techniques such as fiber optic sensors and DIC.…”
Section: Compression-induced Fatigue Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…The propagation of fatigue at the structural level has been recently investigated experimentally in several studies. 108,122,123 An example of the monitored propagation of fatigue degradation in an externally prestressed beam 108 is shown in Figure 6a. The test setup provided detailed data on the structural compressive fatigue behavior of concrete along with the strain field evolution during the fatigue life using advanced measurement techniques such as fiber optic sensors and DIC.…”
Section: Compression-induced Fatigue Propagationmentioning
confidence: 99%
“…The simulation of compressive fatigue propagation at the structural level using a simplified lifetime-based approach has been developed. 122,129 The primary objective of this approach is its applicability to large scale testing and high-cycle fatigue scenarios. This model adapts the linear elastic material model by introducing a reduction of the material stiffness at a certain number of loading cycles based on the uniaxial additive strain model proposed.…”
Section: Modeling Of Multiaxial Fatigue Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Darauf aufbauend wurden später weitere praxisnähere Modelle entwickelt, z. B. in [11][12][13][14][15][16][17]. Jedoch werden diese Modelle vorrangig in der Forschung in eigens dafür entwickelten Softwareumgebungen zur Untersuchung gezielter Problemstellungen angewandt und weniger für allgemeine Anwendungen in der Bemessungspraxis.…”
Section: Introductionunclassified
“…It was observed that the stresses of the higher stressed fiber of the cross‐section (i.e., the upper fiber) decreased and redistributed to the lower fibers during fatigue life. Experimental investigations on large‐scale beam specimens using a resonance‐based testing facility 28 have been recently presented by Birkner and Marx, 2019 29,30 . The evaluation of the experimental tests showed a larger stiffness reduction at the top edge than in the middle of the cross‐section as well as stress redistributions from outer to inner fibers, which have a positive effect on the fatigue lifetime of concrete structures.…”
Section: Introductionmentioning
confidence: 99%